From First to Last: A Few Notes from Sharp 2018 Conference in Sydney - Gudinavičius, Arūnas (Knygotyra, 2018)
This was the first time that the annual conference of the Society for the History of Authorship, Reading and Publishing (SHARP) has been held outside Europe and North America in its 25-year history. The conference took place at Western Sydney University on its historic Parramatta South campus, in the multicultural heart of Western Sydney. More about SHARP 2018 can be found Online: http://sharp2018.sydney.